Effect of integrating student-developed videos into a virtual environment - Yin, Khoo Yin; Ramdan, Mohamad Rohieszan (International Journal of Evaluation and Research in Education (IJERE), 2025)
Many users experience loneliness’ and feel disconnected from teachers and friends during online learning. Lack of engagement between teacher and students can hinder learning and lead to unpleasant feelings such as anxiety and a lack of motivation. Hence, some lecturers require students to develop videos in pairs and share them with peers. The purpose of this study was to measure the effect of integrating of student-developed videos into a virtual environment. The quasi-experimental method with was conducted to investigate students’ perceptions of interest, motivation, engagement and performance. A total of 333 students was divided into experimental and control group. Results showed a positive impact of this approach, which can draw out students’ creativity and their understanding of the content knowledge to integrate these with information and communication technology skills. Examination of the qualitative results suggest that the students need to be closely monitored while making the video to prevent free-riders. This study also recommends that the design of the video must be integrated into the course in order to achieve the learning outcome. This study contributed to literature on the effect of student-developed videos.